2012
DOI: 10.1074/jbc.m112.349811
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Intensity Shock Wave Promotes the Adhesion and Migration of Rat Osteoblasts via Integrin β1-mediated Expression of Phosphorylated Focal Adhesion Kinase

Abstract: Background:The effects of extracorporeal shock wave (ESW) on adhesion and migration of osteoblasts have not been reported until now. Results: Optimal intensity shock wave promotes osteoblast adhesion and migration. Conclusion: ESW promotes the adhesion and migration of osteoblasts via integrin ␤1-mediated expression of phosphorylated FAK.Significance: This provides a mechanistic basis for improving the effectiveness of ESW treatment in fracture healing and tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 67 publications
(70 reference statements)
1
70
0
Order By: Relevance
“…Although the amplitude of the FAK response to the peptides was modest in mMSCs, the increase in FAK in these cells was close to that induced by PDGF, which was used as a positive control. The amplitude of the FAK response to the peptides is also consistent with the reported increase in FAK activity during osteoblast differentiation (52,53). The finding that all peptides increased FAK levels in MSCs indicates that the full RRET sequence is not required for FAK activation evoked by peptideinduced ␣5␤1 integrin priming in MSCs.…”
Section: Rret-dependent Msc Adhesion On Fn-supporting
confidence: 83%
“…Although the amplitude of the FAK response to the peptides was modest in mMSCs, the increase in FAK in these cells was close to that induced by PDGF, which was used as a positive control. The amplitude of the FAK response to the peptides is also consistent with the reported increase in FAK activity during osteoblast differentiation (52,53). The finding that all peptides increased FAK levels in MSCs indicates that the full RRET sequence is not required for FAK activation evoked by peptideinduced ␣5␤1 integrin priming in MSCs.…”
Section: Rret-dependent Msc Adhesion On Fn-supporting
confidence: 83%
“…After establishing HI for the 0, 6, 12, 18, 24, and 36 h time points, rats from different groups were euthanized. RT-PCR experiments and analysis of results were performed as described previously (34) to evaluate the mRNA expression pattern of Cygb under HI conditions. Then we conducted HI treatment within specific time windows (the time for reaching the peak of endogenous Cygb mRNA up-regulation) to rats that had been given saline, ADV only, shRNA, or cDNA treatment to reveal expression of the potential candidates, including Hif-1␣ (hypoxia-inducible factor 1␣) Vegf, caspase-2, and caspase-3.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was shown that the expression of transmembrane integrins on the surface of osteoblasts, specifically α5β1, which mediate the interactions between the ECM and the cells, is increased in response to ESWT [7]. Downstream, several intracellular signal transduction pathways were identified which are stimulated by ESWT.…”
Section: Working Mechanism Of Eswtmentioning
confidence: 99%
“…Downstream, several intracellular signal transduction pathways were identified which are stimulated by ESWT. The focal adhesion kinase (FAK) complex has been implicated to be essential for transmitting extracellular signals to the cell cytoplasm and was seen to be increased phosphorylated not only by integrins [7] but also by ATP [10]. Further intracellular participants of the signaling cascade triggered by various stimuli (e.g.…”
Section: Working Mechanism Of Eswtmentioning
confidence: 99%
See 1 more Smart Citation